Equality in Isolation: Virtual Mobility, Accessibility, and Belonging - Yeoh, Pei Ann (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
This article follows the pandemic practice of The London Improvisers Orchestra between April and June 2020 from the perspective of a Malaysian musician. Virtual mobility and accessibility, isolation and belonging: traits and tropes of the COVID-19 life.